Hematoma expansion is more frequent in deep than lobar intracerebral hemorrhage. (15th December 2020) - Roh, David; Boehme, Amelia; Young, Codi; Roth, William; Gutierrez, Jose; Flaherty, Matthew; Rosand, Jonathan; Testai, Fernando; Woo, Daniel; Elkind, Mitchell S.V.
Abstract : Objective: To test the hypothesis that patients with deep intracerebral hemorrhage (ICH) would encounter hematoma expansion (HE) more frequently compared to patients with lobar ICH. Methods: Patients with ICH with neuroimaging to calculate HE were analyzed from the multicenter Ethnic/Racial Variations of Intracerebral Hemorrhage (ERICH) cohort. Patients with laboratory coagulopathy or preceding anticoagulant use were excluded to assess relationships of ICH location alone (deep vs lobar) with HE, defined as >33% relative growth. Odds ratios (ORs) and 95% confidence intervals (CIs) for these relationships were estimated with logistic regression. Sensitivity and specificity determined HE thresholds best associated with poor 3-month outcomes (modified Rankin score 4-6) stratified by location. Results: There were 1, 049 patients with deep and 408 patients with lobar ICH analyzed. Deep ICH locations were more likely to have HE (adjusted OR 1.57, 95% CI 1.08–2.29) after adjustment for age, sex, race, baseline hematoma size, and intraventricular hemorrhage. However, this difference was nonsignificant (adjusted OR 1.35, 95% CI 0.81–2.24) after controlling for time from symptom onset to admission CT in a subgroup analysis of 729 patients with these data. Yet, the threshold of HE best associated with poor outcomes was smaller in deep (30%) compared to lobar (50%) ICH. Conclusions: While HE was more frequent in deep than lobar ICH, this could be due to differences in symptom onset to admission CT times in our cohort. However, patients with deep ICH appear particularly vulnerable to the deleterious effects of small volumes of HE. Further studies should clarify whether ICH location needs to be considered in HE treatment paradigms.